The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1806-9061-2016-0240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Amounts of Blue Lupine (L. Angustifolius L.) in The Diets of Heavy-Type Turkeys on Their Growth Rate, Carcass and Meat Qualities

Abstract: A study was carried out to determine the effects of soybean meal replacement with different amounts of blue lupine in the diets of turkeys on the growth rate, anatomic carcass dissection data, chemical indicators of breast and thigh muscles and the content of tryptophan and oxyprolin. In total three hundred and sixty cross BIG-6 turkeys were allotted to two control and ten experimental groups of 30 one-dayold turkeys. The control group of turkeys was fed the diet containing soybean meal, whereas the trial grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the literature, blue lupine can be incorporated in broilers' diets in up to 25% of soybean meal protein and yield similar results to the soybean meal (16,18) and white lupine diets (21,22). Other researchers found that when blue lupine is fed at 30% of soybean meal protein (19,40,49) and 15% it does not have any negative influences on the production performance and health of layers (8), but increasing blue lupine to 40 and 80% of soybean meal protein decreased growth and impaired gut ecosystem and increased wet dropping (18,19). Similar results were obtained with the inclusion of 25-30% of blue lupine in turkey diets (40,49).…”
Section: Growth Performancementioning
confidence: 87%
See 2 more Smart Citations
“…In the literature, blue lupine can be incorporated in broilers' diets in up to 25% of soybean meal protein and yield similar results to the soybean meal (16,18) and white lupine diets (21,22). Other researchers found that when blue lupine is fed at 30% of soybean meal protein (19,40,49) and 15% it does not have any negative influences on the production performance and health of layers (8), but increasing blue lupine to 40 and 80% of soybean meal protein decreased growth and impaired gut ecosystem and increased wet dropping (18,19). Similar results were obtained with the inclusion of 25-30% of blue lupine in turkey diets (40,49).…”
Section: Growth Performancementioning
confidence: 87%
“…These results are in agreement with those reported by (40) who observed that 14.0-25.7% of white lupine in broilers' and turkeys' diets has no adverse effect on slaughter yield and carcass quality. In addition, (49) noticed that 25-30% of blue lupine does not significantly affect the dressing percentage, edible parts, and abdominal fat of turkeys. On the other hand, (55) demonstrated that probiotics at 100 and 150 g/ton feed containing Bacillus spp.…”
Section: Carcass Traits Of 21 and 35 D-old Broilersmentioning
confidence: 95%
See 1 more Smart Citation
“…Growers should pay particular attention to raw potato skins, which are particularly dangerous to poultry. Lupine contains quinolizidine alkaloids, which may deteriorate the nutritional and organoleptic quality of poultry meat, and cause nervousness, depression, muscle tremors and convulsions in birds [109]. Lobelia contains toxins belonging to the pyridine alkaloids that can cause neurological changes, weakness, faster breathing and lack of motor coordination in poultry.…”
Section: The Harmful and Toxic Plants For Poultrymentioning
confidence: 99%